A new vertebrate fossil-bearing layer in the Rhætelv Formation (Kap Stewart Group) of central East Greenland: evidence of a Hettangian marine incursion into the continental Jameson Land Basin - Clemmensen, Lars; Lindström, Sofie; Mateus, Octávio; Mau, Malte; Milan, Jesper; Kent, Dennis V. (2021)
The Kap Stewart Group (Rhaetian-Sinemurian, Triassic–Early Jurassic) of the Jameson Land Basin in central East Greenland has traditionally been regarded as a strictly continental unit with delta and perennial lake sediments. New finds of plesiosaur bone remain in a thin storm deposited sandstone bed in the middle part of the Rhætelv Formation of the Kap Stewart Group, however, indicates a likely period of marine influence. At the study area at the eastern margin of the basin, the Rhætelv Formation is 300-m thick and overlies unconformably the Norian Fleming Fjord Group. The bone-bearing sandstone occurs 190 m above the base of the group and is closely associated with black laminated mudstones; palynological investigation of three samples from these mudstones indicates that they are of a younger Hettangian age. The Hettangian was a relatively short stage (201.3–199.5 Ma) and elsewhere characterized by two episodes of sea-level highstands. Assuming that the marine incursion in the Jameson land Basin evidenced by the plesiosaur fossil remains took place during the youngest of these sea-level highstands, the bone-bearing bed of the Rhætelv Formation can be dated to 200 Ma and thereby gives the first numerical age constraint of this hitherto poorly dated succession.